2020
DOI: 10.1007/s10571-019-00784-3
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Role of Astrocytes in Subthalamic Nucleus Deep Brain Stimulation in a Parkinson’s Disease Rat Model

Abstract: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is an effective therapeutic strategy for motor symptoms of Parkinson's disease (PD) when L-DOPA therapy induces disabling side effects. Classical inflammatory activation of glial cells is well established in PD, contributing to the progressive neurodegenerative state; however, the role of DBS in regulating the inflammatory response remains largely unknown. To understand the involvement of astrocytes in the mechanisms of action of DBS, we evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 102 publications
4
15
0
Order By: Relevance
“…After DBS electrode implantation, regional neuroinflammation in the rats was observed with concomitant memory impairment (Hirshler et al 2010 ); in the macaque, reactive gliosis was seen after 3 months and 3 years (Griffith and Humphrey 2006 ); and in the human, reactive gliosis was observed in a postmortem study 12 years after implantation in an essential tremor patient with good tremor control (DiLorenzo et al 2010 ). Recent study by Campos et al ( 2020 ) showed that DBS activated astrocytes and prevented TNF-α-induced increase of monocyte chemoattractant protein-1 (MCP-1) and NF-κB activation in vitro. In the same study, 6-OHDA microinjection into the SN induced an increase in the number of GFAP-positive cells in the globus pallidus (GP) 13 days after PD model induction, but also influenced IFN-γ induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After DBS electrode implantation, regional neuroinflammation in the rats was observed with concomitant memory impairment (Hirshler et al 2010 ); in the macaque, reactive gliosis was seen after 3 months and 3 years (Griffith and Humphrey 2006 ); and in the human, reactive gliosis was observed in a postmortem study 12 years after implantation in an essential tremor patient with good tremor control (DiLorenzo et al 2010 ). Recent study by Campos et al ( 2020 ) showed that DBS activated astrocytes and prevented TNF-α-induced increase of monocyte chemoattractant protein-1 (MCP-1) and NF-κB activation in vitro. In the same study, 6-OHDA microinjection into the SN induced an increase in the number of GFAP-positive cells in the globus pallidus (GP) 13 days after PD model induction, but also influenced IFN-γ induction.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, 6-OHDA microinjection into the SN induced an increase in the number of GFAP-positive cells in the globus pallidus (GP) 13 days after PD model induction, but also influenced IFN-γ induction. In addition, 6-OHDA-induced IFN-γ was completely attenuated by DBS-STN (Campos et al 2020 ). The above data suggests that in both stimulated groups, the peripheral immunity changes after DBS-STN could depend on the combined neuronal–glial interactions and influence on hormone balance.…”
Section: Discussionmentioning
confidence: 99%
“…The PD induction model was made as previously described [ 25 , 54 ]. Animals were anesthetized with isoflurane (4% induction, 2.5% maintenance in 100% oxygen) associated with local anesthesia (2% lidocaine, 100 μL/animal on the scalp).…”
Section: Methodsmentioning
confidence: 99%
“…This has been used successfully to detect neuroinflammation in cortical and subcortical regions in intervention studies and neurological disorders such as PD, AD and epilepsy (Gershen et al, 2015 , Jucaite et al, 2015 , Sandiego et al, 2015 , Kreisl et al, 2017 ). Modulation of neuroinflammatory response by DBS has been suggested as a potential therapeutic strategy in animal models of neurodegenerative diseases (Campos et al, 2020 , Chen et al, 2020 ) although this has not been demonstrated in patient populations. Nevertheless, VNS has been shown to impact immunity in the brain and many other organ systems upstream and downstream the site of stimulation (Pavlov, 2019 ).…”
Section: Development Of New Frontiersmentioning
confidence: 99%